Insomnia, sleep loss, and circadian sleep disturbances in mood disorders: a pathway toward neurodegeneration and neuroprogression? A theoretical review - Palagini, Laura; Geoffroy, Pierre A.; Miniati, Mario; Perugi, Giulio; Biggio, Giovanni; Marazziti, Donatella; Riemann, Dieter (CNS spectrums, 2022)
The present paper aims at reviewing and commenting on the relationships between sleep and circadian phasing alterations and neurodegenerative/neuroprogressive processes in mood disorder. We carried out a systematic review, according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, in PubMed, PsycINFO, and Embase electronic databases for literature related to mood disorders, sleep disturbances, and neurodegenerative/neuroprogressive processes in relation to (1) neuroinflammation, (2) activation of the stress system, (3) oxidative stress, (4) accumulation of neurotoxic proteins, and (5) neuroprotection deficit. Seventy articles were collectively selected and analyzed. Experimental and clinical studies revealed that insomnia, conditions of sleep loss, and altered circadian sleep may favor neurodegeneration and neuroprogression in mood disorders. These sleep disturbances may induce a state of chronic inflammation by enhancing neuroinflammation, both directly and indirectly, via microglia and astrocytes activation. They may act as neurobiological stressors that by over-activating the stress system may negatively influence neural plasticity causing neuronal damage. In addition, sleep disturbances may favor the accumulation of neurotoxic proteins, favor oxidative stress, and a deficit in neuroprotection hence contributing to neurodegeneration and neuroprogression. Targeting sleep disturbances in the clinical practice may hold a neuroprotective value for mood disorders.